2005
DOI: 10.1097/01.ijg.0000176933.14229.fc
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Pole Retinal Thickness in Ocular Hypertension and Glaucoma

Abstract: The RTA can reveal increased hemispheric thickness asymmetries in both OHT and OAG eyes. In OAG eyes thickness asymmetries are associated with corresponding perimetric asymmetries. The findings in OHT eyes suggest that localized anatomic and functional damage to inner retina may not develop in parallel early in the disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Horizontal hemifield asymmetry has been shown to be valuable in assessment of early glaucomatous changes. 24,33,34 Similarly, in our study, the relationships between GCIPL and MS asymmetries exhibited higher correlations than did direct comparisons between GCIPLT and MS.…”
Section: Discussionsupporting
confidence: 58%
“…Horizontal hemifield asymmetry has been shown to be valuable in assessment of early glaucomatous changes. 24,33,34 Similarly, in our study, the relationships between GCIPL and MS asymmetries exhibited higher correlations than did direct comparisons between GCIPLT and MS.…”
Section: Discussionsupporting
confidence: 58%
“…Bagga et al [17] showed that a macular thickness symmetry test had the potential to detect glaucomatous damage using TD-OCT. Salgarello et al [18] reported that hemispheric asymmetry in glaucomatous eyes increased compared with the control group using RTA. These results are in agreement with our report where macular symmetry testing values of PG eyes were significantly different from those of control eyes using SD-OCT measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, horizontal hemifield asymmetry is regarded as very useful in the assessment of early glaucomatous changes as it measures disparity in macular thickness between superior and inferior zone [17,18]. Glaucomatous damage usually commences in only one horizontal hemifield and is assessed using the glaucoma hemifield test, which measures the disparity in retinal sensitivity between the superior and inferior hemifields [19].…”
Section: Introductionmentioning
confidence: 99%
“…RNFL thickness asymmetry can be an early sign of glaucomatous damage and has been explored by OCT technology using 2 main methods: (1) assessing RNFL thickness asymmetry between vertically opposing quadrants of the same eye 41,46,[50][51][52][53] ; and (2) assessing intereye RNFL asymmetry for global average and for quadrants and sectors. [41][42][43][44][45][46]53,54 This study focuses on asymmetry analysis using the second method and demonstrates that OAG eyes exhibit significantly greater intereye mean RNFL asymmetry compared with normal eyes (Fig.…”
Section: Discussionmentioning
confidence: 99%